Reframing Vocational English Curriculum Design: A Twelve-Pillar Model for Sustainable and Industry-Aligned ELT - Faizatus Sholihah; Nirwanto Maruf (English Department - University of Sultan Ageng Tirtayasa, 2026)
English curriculum design in Technical and Vocational Education and Training (TVET) is undergoing significant transformation due to rapid technological change, global labour mobility, and the increasing role of English as a professional lingua franca. However, existing ESP and vocational curriculum frameworks often conceptualize curriculum components in isolation, resulting in fragmented design and limited alignment with workplace communication demands. Addressing this gap, this study proposes a twelve-pillar ecological framework that reconceptualizes vocational English curriculum as an interconnected system across macro (policy), meso (program), and micro (pedagogy) levels. The framework is developed through a systematic conceptual synthesis of peer-reviewed literature published between 2020 and 2025, identified through structured searches in Scopus, Web of Science, ERIC, and Google Scholar using predefined inclusion and exclusion criteria. The synthesis suggests that effective vocational English curricula require the integration of philosophical grounding, needs analysis, competence-based design, task-based pedagogy, digital learning, inclusion, teacher agency, and continuous evaluation within a unified structure. This study contributes a theoretically grounded and operationally adaptable framework that extends existing curriculum models by embedding sustainability, digital transformation, and social inclusion as core structural dimensions. The framework offers practical guidance for aligning vocational English education with contemporary workplace communication practices while also outlining directions for future empirical validation.